Entry Strategy and Survival of De Novo New Ventures - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2006)
This paper provides an integrated analysis on de novo entrants, linking their management experience, strategic orientation and market entry decisions to their survival in a single analysis. We rely on a census of new ventures in the intra-European scheduled airline industry. Contrary to predictions in the existing literature, we find that those entrants focusing on new as opposed to existing markets report significantly higher chances of survival than their peers. Given the industrial context, we expected a low-cost orientation to enhance survivability among new entrants but did not find evidence of this as a viable entry strategy. Finally, contrary to existing evidence, entrant survivability does not improve as with time. Instead, it is aided significantly by prior management experience in the industry.